Needs Analysis of Augmented Reality (AR) Based Learning Media Development in Road and Bridge Construction Subjects - Khofifah Alawyah; Giatman; Fahmi Rizal; Dedy Irfan (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study is to analyze the needs of students in the development of Augmented Reality (AR) media on food chain material. This research is classified into development research developed with the ADDIE model. It's just that the research was only carried out at the analysis stage, namely material analysis and needs analysis.   The subjects involved in this study were teachers and students of XI 1 DPIB. Data collection in the study was carried out using the literature study method and interviews. The research instrument used is the teacher and student media needs interview sheet.  The data obtained in the study were then analyzed descriptively quantitatively and qualitatively.  Quantitative analysis was carried out to analyze the results of the questionnaire using the percentage formula, while qualitative analysis was carried out by describing the results of the research and relating them to the results of previous studies. The results showed that the concept in the material analysis of bridge parts material contained 25% concrete and 75% abstract. And based on field studies, teachers and students in learning only use printed books from schools, so they are unable to show the 3 dimensions of an object.  Teachers and students also need to improve the use of media, one of which can use A-media.